Forensic Traceological Analysis of Works of Visual Arts - Sh. N. Khaziev (Теория и практика судебной экспертизы)
The article discusses the fundamentals of traceological forensic analysis of visual artworks within both the framework of forensic traceological examination and comprehensive forensic research with the participation of expert-traceologists. Works of art are investigated to identify them, diagnose their condition, and establish the origin of various negative changes. Forensic traceology methods can play an essential role in the controversial attributions of paintings, drawings, and sculptures. The necessity and feasibility of developing a modern forensic traceological research methodology of fine artworks are substantiated.